A brief history of hyperinflation in Argentina - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
A fiscal deficit of 8.5% of GDP, limited access to credit locally and internationally, country risk premiums at default levels and money supply growing at 80% annually, have led some analysts to predict that Argentina might be heading into a "3-digit modern hyperinflation." Although this opinion is not widely held, the consensus inflation forecast for 2021 is 47%, a level significantly below any definition of hyperinflation but high by global standards (above the 98th percentile). Even more worrisome, over the last decade inflation has shown a persistent upward trend and since January 2019 has averaged 45%. Given all of the above, it is worthwhile investigating when Argentina experienced it and why. This paper attempts to answer the first part of this question. According to a widely accepted view there was only one hyperinflation between 1989 and 1990. This paper argues that Argentina experienced four hyperinflationary episodes that were part of a long-term cycle that started in 1945.
Keywords: E31; N16; 330; Argentina; Inflation; Extreme Inflation; Hyperinflation